Implementasi Pengembangan Media Pembelajaran Kartu Kuartet dalam Menanamkan Nilai-Nilai Pancasila - Priabudi, Danang; Nuruddin, Muhammad (IJPSE Indonesian Journal of Primary Science Education, 2024)
The Learning at SDN Jatirejo Jombang still uses conventional methods such as lectures. Students have never used quartet media. Based on this, there is a need for new innovations such as producing quartet card media to increase the learning knowledge of SDN Jatirejo Jombang students. The development of quartet card media is carried out using the Research and Development (RnD) method with the Borg and Gall model because it is considered appropriate. There are 7 stages to go through 1) Potential and problems, 2) Research and data collection, 3) Product design planning, 4) Design validation, 5) Design improvement, 6) Product testing, and 7) Product revision. Based on the results of the data during the study: 1) the quartet card media developed was declared very valid for use in learning. This is based on the validation results of media experts of 85.26% and material experts 95.80% of the percentage of criteria that have been set. 2) The quartet card media developed is declared very suitable for use in learning. This is based on the results of the teacher response questionnaire 92.59%, the student response questionnaire product trials 95.78%.